Flux-quantum-discretized dynamics of magnetic flux entry, exit, and annihilation in current-driven mesoscopic type-I superconductors - Berdiyorov, G. R. (2012)
We study nonlinear flux dynamics in a current-carrying type-I superconductor. The stray magnetic field of the current induces the intermediate state, where nucleation of flux domains is discretized to a single fluxoid at a time, while their final shape (tubular or laminar), size, and nucleation rate depend on applied current and edge conditions. The current induces opposite flux domains on opposite sides of the sample, and subsequently drives them to annihilation-which is also discretized, as a sequence of vortex-antivortex pairs. The discretization of both nucleation and annihilation leaves measurable traces in the voltage across the sample and in locally probed magnetization. The reported dynamic phenomena thus provide an unambiguous proof of a flux quantum being the smallest building block of the intermediate state in type-I superconductors.